The man who broke into Auschwitz : a true story of World War II - Avey, Denis, 1919-; Broomby, Rob. (Cambridge, MA : Da Capo Press, 2011)
Tells the true story of a British soldier who was held in a POW labor camp in the summer of 1944 and willingly smuggled himself into the Buna-Monowitz concentration camp --known as Auschwitz III--to witness firsthand the cruelty there.
Keywords: Avey, Denis, -- 1919-; Avey, Denis, -- 1919-; Monowitz (Concentration camp); Monowitz (Poland: Concentration camp); World War, 1939-1945 -- Prisoners and prisons, German; World War, 1939-1945 -- Personal narratives, British; Holocaust, Jewish (1939-1945) -- Poland; World War, 1939-1945 -- Prisoners and prisons; World War, 1939-1945 -- Personal narratives; Holocaust, 1939-1945.